North American apple-tree species: sources of useful agronomic traits for breeding - O. N. Barsukova (Труды по прикладной ботанике, генетике и селекции)
The results of studying the collection of North American apple-tree species are presented. Forms with a whole set of traits interesting for breeding are highlighted, including such features as late flowering schedule, disease resistance, long shelf life of fruits, etc. In addition, the small-fruited ornamental apple-tree (crab apple) accessions obtained from North American species are briefly described, and the most valuable of them are recommended for practical uses.